The impact of firm-level and project-level it capabilities on CRM system quality and organizational productivity - Suoniemi Samppa; Terho Harri; Zablah Alex; Olkkonen Rami; Straub Detmar W. (Elsevier Inc., 2022)
While CRM technology implementation initiatives frequently end up as failures, most research has focused on user related reasons for understanding low success rates. This study extends CRM research backwards into the system implementation phase to improve understanding of the hitherto unexplored technical antecedents of CRM success. We advance a resource-based theory of CRM system capability (CRMSC) to explain how firm- and project-level capabilities act to influence organizational performance. Empirical findings from a survey matching 148 IT manager and 474 end-user responses support the conceptualization of CRMSC as a project-level capability, and suggest that CRMSC and system quality mediate the effects of firm-level IT capability on organizational productivity gains and productivity gain discrepancy. The study complements extant understanding about the link between strategic and operational IT capabilities by offering actionable insight on the combination of resources firms need to deliver a CRM system that enhances performance.